The Design of a Multi-touch Gestural System for Semi-autonomous Driving - Hammar, Joel; Karlsson, Andreas (My University, 2015)
With more and more advanced technology being developed, the need of human interaction is no longer as prominent as before. Especially in the automotive industry where autonomous vehicles come closer to being introduced to the consumer market. However, by introducing automation the role of the driver is changing from being the operator of the vehicle to becoming a supervisor of the automation state (Damböck et al. 2012). That can lead to potential problems where the driver becomes less aware of the current situation and the reaction time in case of system failure is increased (Endsley and Kiris 1995; Neimann, Peterman, and Manzey 2011). In order to address this problem we have designed a multi-touch gestural system for semi-autonomous driving, which enables the driver to influence the driving by giving instructions, such as change lane or take next exit/turn to the vehicle while it is in autonomous mode. The process towards designing the system included several iterations. In the first and second iteration the focus was on understanding the domain of gestures and which gestures that are most natural for giving the vehicle instructions. Then in the third iteration the focus progressed towards designing multimodal feedback and evaluating the complete system in a high-fidelity simulator. Lastly, a few changes were made in the design of the system according to the data gathered from the evaluation. Conclusions that can be drawn from this study is that the users seem to prefer gestures which aims to resemble the movement of the vehicle. Furthermore, the results indicate the single finger gestures are prefered rather than multi-touch and that the gestures should be designed to be as simple as possible in terms of gestural motion. Additionally, the feedback should be instantaneous and multimodal (visual and auditory), as multimodality seem to convey a richer message to the user than if the modalities were to be used separately.
Keywords: Människa-datorinteraktion (interaktionsdesign); Human Computer Interaction